Integrating Information Technologies Into Business Functions: A Taxonomy of Integration Strategies - Alkhatib, Ghazi I. (2020)
The objective of this paper is to establish a taxonomy of integration strategies that will assist information technology managers in integrating information technologies into business functions and strategies. Such integration is becoming even more of a reality now because of several factors: increased capabilities of inter-networking, availability of development tools that permit multi-platform interfaces, and the evolution of distributed databases. The paper provides a scheme for defining integration that identifies three dimensions: scope, object, and organization. Objectives of integration are classified into gaining competitive advantage, achieving more effective and efficient operations, and improving customer relations. The taxonomy of integration strategies is presented based on the following layers of platforms: information technologies, network, data base, application development, and organization strategies. An integration project may include one or more dimension, achieve one or more objectives, and span over one or more platforms. Without proper planning and implementation, integration projects may fail causing the loss of technology and financial resources.